1998
DOI: 10.2134/jeq1998.00472425002700060034x
|View full text |Cite
|
Sign up to set email alerts
|

Responses of Soil Respiration to Clipping and Grazing in a Tallgrass Prairie

Abstract: Soil‐surface CO2 flux (Fs) is an important component in prairie C budgets. Although grazing is common in grasslands, its effects on Fs have not been well documented. Three clipping treatments: (i) early‐season clipping (EC); (ii) full‐season clipping (FC); and (iii) no clipping (NC); which represented two grazing strategies and a control, were applied to plots in a tallgrass prairie in northeastern Kansas, USA. Measurements of Fs were made with a portable gas‐exchange system at weekly to monthly intervals for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
152
7
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 199 publications
(178 citation statements)
references
References 0 publications
18
152
7
1
Order By: Relevance
“…In wet soils, drought has resulted in an increase of F Soil (Kim et al, 1992;Davidson et al, 2004;Sowerby et al, 2008), while for mesic and drier habitats reduced F Soil or negligible drought effects have been observed (Freeman et al, 1996;Bremer et al, 1998;Harper et al, 2005;Garten et al, 2009). Beside the short-term effects during the drought period itself, we also observed a significant reduction of cumulated F Soil over the entire 13 CO 2 measurement period by 26% from April until October (Tables 3 and 4).…”
Section: Effects Of Droughtsupporting
confidence: 57%
See 1 more Smart Citation
“…In wet soils, drought has resulted in an increase of F Soil (Kim et al, 1992;Davidson et al, 2004;Sowerby et al, 2008), while for mesic and drier habitats reduced F Soil or negligible drought effects have been observed (Freeman et al, 1996;Bremer et al, 1998;Harper et al, 2005;Garten et al, 2009). Beside the short-term effects during the drought period itself, we also observed a significant reduction of cumulated F Soil over the entire 13 CO 2 measurement period by 26% from April until October (Tables 3 and 4).…”
Section: Effects Of Droughtsupporting
confidence: 57%
“…Kim et al, 1992;Sowerby et al, 2008), while studies in mesic and drier habitats observed a reduction of F Soil due to increased plant and microbial stress (e.g. Bremer et al, 1998;Harper et al, 2005;Garten et al, 2009) as well as no or limited effects (Freeman et al, 1996). Furthermore, several sources (auto-and heterotrophic) contribute to F Soil with each of them probably responding differently to changes in precipitation amounts and patterns (Borken et al, 2006;Inglima et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…been shown that CO 2 flux from tallgrass prairie can be reduced by up to 49% within 2 d of clipping (Bremer et al 1998). After hay removal, C fluxes from CWG were similar to those from wheat (Fig.…”
Section: Emissions Of Comentioning
confidence: 68%
“…High temperature sensitivity may include the direct physiological effect of temperature on root and microbial activities and the indirect effect related to photosynthetic assimilation and carbon allocation to roots (Davidson et al, 1998). Evidence for the indirect effect of photosynthesis on autotrophic respiration comes from a series of recent studies (Bremer et al, 1998;Högberg et al, 2001;Bowling et al, 2002). During the dry season, the main portion of ecosystem respiration comes from the more recalcitrant carbon material, which has been shown to have low temperature sensitivity (Liski et al, 1999).…”
Section: Response Of Nighttime F C To Temperaturementioning
confidence: 99%